A Three-Dimensional Hydraulic Stack Model for Redox Flow Batteries Considering Porosity Variations in Porous Felt Electrodes and Bypass Flow in Side Gaps - Xinjie Guan; Maria Skyllas-Kazacos; Chris Menictas (Batteries, 2023)
Redox flow batteries provide high flexibility and scalability for large-scale energy storage systems due to their safety, low cost and decoupling of energy and power. While typical flow frame designs usually assume all parts are standard, the industry can suffer from irregularity and manufacturing tolerances of cell components, such as the shape or dimensions of the flow frame and porous electrode. This paper evaluates the impact of side gaps and porosity differences of the graphite felt due to irregularity and manufacturing tolerances on the electrolyte flow in the active cell areas. A three-dimensional hydraulic model with parameterised multi-cell stack geometry has been developed in COMSOL to compare the cell velocity distributions and pressure losses of a vanadium redox flow battery with flow-through electrodes. The results indicate that the side gaps and porosity segments can result in preferential flow within low-resistance areas, leading to significantly lower flow rates for other cell areas compared with standard flow frames. Proposed countermeasures of adjusting channel locations and applying dimples protruding into the cell cavity from the flow frame show good potential to avoid stagnant zones and maintain theoretical flow rates for the active cell areas.